Microsoft Project For Dummies - Dionisio, Cynthia Snyder (--For dummies., 2022)
Blow past the jargon and get hands-on, practical guidance on managing any project with Microsoft Project Lean. Agile. Hybrid. It seems that project management these days comes with more confusing buzzwords than ever. But you can make managing your next project simple and straightforward with help from Microsoft Project For Dummies. This book unpacks Microsoft's bestselling project management platform and walks you through every important feature, step-by-step, until you're ready to take on virtually any project, no matter the size. From getting set up for the first time to creating tasks, managing resources and working with time management features, you'll learn everything you need to know about managing a project in Microsoft's iconic software. You'll also find: Totally updated guidance that applies to both the desktop version and Microsoft's new subscription-based Microsoft Project Online Helpful information on integrating Agile practices and techniques into your project "Golden rules" that keep a project on-track and on-time Ways to effectively manage your resources with Microsoft Project's built-in functionality Managing a project, big or small, is no easy task. Luckily, Microsoft Project For Dummies can take a lot of the hassle out of your day-to-day life. Learn how to take advantage of this powerful software today!.